(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The rapid development of the digital economy has transformed the financial sector, presenting both challenges and opportunities for commercial banks. This study explores strategies for improving the efficiency of commercial banks within the evolving digital landscape. By integrating advanced digital technologies such as artificial intelligence, blockchain, and big data analytics, banks can enhance operational processes, customer service, and risk management. The research also highlights the importance of digital transformation in maintaining competitive advantage and meeting changing customer expectations. Ultimately, this paper provides practical recommendations for commercial banks to optimize their efficiency and sustainability in the digital economy